Implementasi Pendidikan Lingkungan Hidup Sebagai Pengejawantahan Mandat Budaya Kejadian 1:28 Dalam Gereja Lokal - Frederik, Hanny; Rouw, Randy Frank (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2022)
This article discusses how the church can realize the cultural mandate through environmental education within the scope of the Christian faith community. The method used is descriptive qualitative. The results of this article research are the manifestation of the cultural mandate by the church can occur through the implementation of environmental education within the scope of local churches. Environmental education in the church can be applied to members of the congregation for all ages and groups, because after all environmental education is part of teaching about the Christian faith and environmental conservation is part of the practice of faith. Both must be integrated to create an environmental education curriculum that can be applied in various forms of teaching in the church. There may be challenges for the church in implementing environmental education. The key is actually in the hands of the church leadership, whether they have sensitivity to environmental conditions and the willingness to obey the cultural mandate that God has given them or not. Artikel ini membahas cara gereja dapat mengejawantahkan amanat budaya itu melalui pendidikan lingkungan hidup dalam lingkup komunitas iman Kristen. Metode yang dipergunakan kualitatif deskriptif. Hasil penelitian artikel ini adalah pengejawantahan mandat budaya oleh gereja dapat terjadi lewat pengimplementasian pendidikan lingkungan hidup dalam ruang lingkup gereja-gereja lokal. Pendidikan lingkungan hidup di dalam gereja dapat diterapkan pada anggota jemaat untuk semua kalangan dan golongan usia, karena bagaimanapun juga pendidikan lingkungan hidup adalah bagian dari pengajaran tentang iman Kristen dan pelestarian lingkungan hidup adalah bagian dari praktik iman. Keduanya harus diintegrasikan untuk menciptakan kurikulum pendidikan lingkungan hidup yang dapat diterapkan dalam berbagai bentuk pengajaran di gereja.